Food and Energy Sovereignty as a Pancasila Economic Project: A Study of Soemitro's Book Djojohadikusumo Anti-colonialism - Anang Fahmi Luqmawan Putra; Yudhie Haryono (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The documentary film “Pesta Babi” (Pig Feast) by Watchdoc, along with the accompanying narratives, has sparked a serious debate regarding the National Strategic Projects (PSN) in South Papua—specifically the food estate and bioethanol plantation projects. This article is not intended to silence legitimate criticism; indeed, criticism serves as a healthy vitamin for democracy. Rather, it aims to provide a comprehensive, constitutional, and value-based analytical framework for interpreting the Papua PSN policy through the lenses of